Highly Efficient p‐i‐n Perovskite Solar Cells Utilizing Novel Low‐Temperature Solution‐Processed Hole Transport Materials with Linear π‐Conjugated Structure. Issue 35 (22nd July 2016) - Li, Yang; Xu, Zheng; Zhao, Suling; Qiao, Bo; Huang, Di; Zhao, Ling; Zhao, Jiao; Wang, Peng; Zhu, Youqin; Li, Xianggao; Liu, Xicheng; Xu, Xurong
Abstract : Alternative low‐temperature solution‐processed hole‐transporting materials (HTMs) without dopant are critical for highly efficient perovskite solar cells (PSCs). Here, two novel small molecule HTMs with linear π‐conjugated structure, 4, 4′‐bis(4‐(di‐ p ‐toyl)aminostyryl)biphenyl (TPASBP) and 1, 4′‐bis(4‐(di‐ p ‐toyl)aminostyryl)benzene (TPASB), are applied as hole‐transporting layer (HTL) by low‐temperature (sub‐100 °C) solution‐processed method in p‐i‐n PSCs. Compared with standard poly(3, 4‐ethylenedioxythiophene): poly(styrenesulfonic acid) (PEDOT:PSS) HTL, both TPASBP and TPASB HTLs can promote the growth of perovskite (CH3 NH3 PbI3 ) film consisting of large grains and less grain boundaries. Furthermore, the hole extraction at HTL/CH3 NH3 PbI3 interface and the hole transport in HTL are also more efficient under the conditions of using TPASBP or TPASB as HTL. Hence, the photovoltaic performance of the PSCs is dramatically enhanced, leading to the high efficiencies of 17.4% and 17.6% for the PSCs using TPASBP and TPASB as HTL, respectively, which are ≈40% higher than that of the standard PSC using PEDOT:PSS HTL. Abstract : Two novel small molecular materials are explored as the hole‐transporting layer in p‐i‐n perovskite solar cells (PSCs), yielding high efficiencies of 17.4% and 17.6%, respectively, which are ≈40% higher than the standard PSCs.